2014
DOI: 10.1002/mop.28166
|View full text |Cite
|
Sign up to set email alerts
|

Graphene microwave absorber: Transparent, lightweight, flexible, and cost‐effective

Abstract: This article presents the graphene as microwave absorber using polyurethane as substrate. The samples were characterized with Raman spectrometer, optical microscope, and vectorial network analyser. The results show a chemical vapor deposition‐grown graphene‐based device that can be used as microwave absorber for its unique characteristics of flexibility, transparency, light‐weight, cost‐effectiveness, and RF shielding. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:560–563, 2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…In particular, graphene has been seen as a potential substitute for ITO in the broader field of transparent conductors. However, the SE of monolayer graphene is only 2.27 dB when produced by chemical vapor deposition (CVD) in the microwave range, , which is insufficient for most EMI shielding applications require SE larger than 10 dB or even larger than 20 dB at some cases. Moreover, a majority of the reported graphene-based materials for EMI shielding are opaque or offer poor transparency for high EMI SE. Recently attempts have focused on improving the EMI shielding performance of transparent graphene-based materials to address these issues. An example can be seen in work done by Hong et al which showed a SE of 6.91 dB at 2.2–7 GHz for triple-layer CVD graphene . Kim et al also reported a SE of 6.37 dB at 0.5–8.5 GHz with a light transmittance of 62% for reduced graphene oxide (RGO) sheets interleaved between poly­(ether imide) (PEI) films fabricated by electrophoretic deposition (EPD) .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, graphene has been seen as a potential substitute for ITO in the broader field of transparent conductors. However, the SE of monolayer graphene is only 2.27 dB when produced by chemical vapor deposition (CVD) in the microwave range, , which is insufficient for most EMI shielding applications require SE larger than 10 dB or even larger than 20 dB at some cases. Moreover, a majority of the reported graphene-based materials for EMI shielding are opaque or offer poor transparency for high EMI SE. Recently attempts have focused on improving the EMI shielding performance of transparent graphene-based materials to address these issues. An example can be seen in work done by Hong et al which showed a SE of 6.91 dB at 2.2–7 GHz for triple-layer CVD graphene . Kim et al also reported a SE of 6.37 dB at 0.5–8.5 GHz with a light transmittance of 62% for reduced graphene oxide (RGO) sheets interleaved between poly­(ether imide) (PEI) films fabricated by electrophoretic deposition (EPD) .…”
Section: Introductionmentioning
confidence: 99%
“…The large interfacial impedance gap inevitably leads to a large reflection coefficient and thus adversely affects the performance of CVD‐grown graphene absorbers. For instance, Barbosa et al prepared CVD‐grown graphene for use as a microwave absorber by using polyurethane (PU) as a substrate . Although this device exhibited flexibility and transparent properties, its absorption loss was negligible.…”
Section: Graphene‐based Materials For Microwave Absorptionmentioning
confidence: 99%
“…The sample is characterized with Raman spectrometer, optical microscope, and vectorial network analyzer. On the basis of experimental results, authors concluded that graphene can effectively replace the conventional microwave-absorbing materials due to its unique characteristics of flexibility, tunability, transparency, lightweight, costeffectiveness, and RF shielding [50].…”
Section: Dielectric Nanocompositesmentioning
confidence: 99%